Ultrastructure of the lorica of species (Euglenophyta) from New Jersey, USA - Conforti, Visitacion Teresa D. (2010)
A floristic and ultrastructural study on Trachelomonas was made in the piedmont region of central New Jersey, USA, where a large number of euglenoid taxa are contained in several freshwater bodies. Abundant and unusual loricated species were found during the observations of samples from these ponds. From the forty-seven taxa determined, eighteen are reported for the first time in the USA. Detailed ultrastructure examination with scanning electron microscopy (SEM) yielded interesting results. Among the taxa described in this work T. compacta var. parvicollis is proposed as new variety, and four are considered affinis to described taxa, T. bacillifera var. collifera, T. granulosa, T. raciborskii var. incerta and T. verrucosa var. verrucosa fo. irregularis, respectively. Twelve taxa are examined and documented, for the first time ever, with original SEM micrographs.